1995
DOI: 10.1016/0370-2693(94)01694-8
|View full text |Cite
|
Sign up to set email alerts
|

On realizing the bosonic string as a noncritical W3-string

Abstract: We discuss a realization of the bosonic string as a noncritical W 3 -string. The relevant noncritical W 3 -string is characterized by a Liouville sector which is restricted to a (non-unitary) (3, 2) W 3 minimal model with central charge contribution c l = −2. Furthermore, the matter sector of this W 3 -string contains 26 free scalars which realize a critical bosonic string. The BRST operator for this W 3 -string can be written as the sum of two, mutually anticommuting, nilpotent BRST operators: Q = Q 0 + Q 1 i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The string coordinates are called 'matter' fields while the non-decoupled gravitational fields are represented by a set of so-called 'Liouville' fields. In [9,41], the BRST operators for the Liouville system were obtained. Especially, in [37,42] The physical states in string theory can most elegantly be described by using the BRST formalism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The string coordinates are called 'matter' fields while the non-decoupled gravitational fields are represented by a set of so-called 'Liouville' fields. In [9,41], the BRST operators for the Liouville system were obtained. Especially, in [37,42] The physical states in string theory can most elegantly be described by using the BRST formalism.…”
Section: Introductionmentioning
confidence: 99%
“…The string coordinates are called 'matter' fields while the non-decoupled gravitational fields are represented by a set of so-called 'Liouville' fields. In [9,41], the BRST operators for the Liouville system were obtained. Especially, in [37,42], the BRST operators of W M 2,s ⊗W L 2,s ′ were constructed at the classical level, and much valuable results were given.…”
Section: Introductionmentioning
confidence: 99%
“…If one were to bosonise the (r, s) fields in that case, the BRST operator would become the same as the one given in Ref. [6], except that in this paper we use Eqn. (7) rather than a two-scalar realisation for the c = −2 Liouville sector, and use T X + T ξη for the c = 26 effective energy-momentum tensor.…”
Section: The Non-critical W Brst Operator and Its Cohomologymentioning
confidence: 99%
“…Later it was found that this is a general phenomenon: a (super)string with N extended world-sheet supersymmetry can be embedded into a superstring with N +1 extended supersymmetry as a particular vacuum state of the latter. Analogous embeddings were constructed for strings associated with nonlinear W type algebras and their linearizing algebras [8]- [11]. It was suggested that all the known strings and superstrings present different vacua of some hypothetical universal string theory.…”
Section: Introductionmentioning
confidence: 99%
“…An essential peculiarity of this case originating from the nonlinear nature of W and the subalgebra {T m , J m , G + m } become different after passing to the quantum case, but also the structure relations of the latter algebra are modified. Namely, its quantum OPEs are as follows 11) and they differ from the classical ones in that the current G + m acquires an anomalous conformal dimension 3 2 + 9 9−c . Actually, this is none other than the algebra W lin 3 which linearizes another kind of nonlinear algebra, Zamolodchikov's W 3 algebra [20].…”
mentioning
confidence: 99%